2018
DOI: 10.1021/acsami.8b10991
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Laser-Induced Graphene for Nitrogen Sensing in Soil

Abstract: Flexible graphene electronics are rapidly gaining interest, but their widespread implementation has been impeded by challenges with ink preparation, ink printing, and post-print annealing processes. Laser-induced graphene (LIG) promises a facile alternative by creating flexible graphene electronics on polyimide substrates through a one-step laser writing fabrication method. Herein we demonstrate the use of LIG, created through a low-cost UV laser, for electrochemical ion selective sensing of plant-available ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
120
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(125 citation statements)
references
References 61 publications
3
120
1
1
Order By: Relevance
“…However, the underlying conversion mechanism for this method is still unclear, and the key parameters to ensure high‐quality graphene are yet to be identified. A molecular dynamics (MD) simulation study by Dong et al suggests that under extreme conditions of high pressure (≈3 GPa) and temperature (>2400 K), which mimic those generated by the infrared laser induction, it is possible to form crystallized layered graphene clusters from PI without the assistance of metal catalysts; this result is consistent with previous experimental observations; on the other hand, recent work show that if UV laser, instead of infrared laser, is used in the conversion process, only very poor quality graphene can be produced, due possibly to the poor absorption of UV light by the carbon source or unoptimized processing conditions.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…However, the underlying conversion mechanism for this method is still unclear, and the key parameters to ensure high‐quality graphene are yet to be identified. A molecular dynamics (MD) simulation study by Dong et al suggests that under extreme conditions of high pressure (≈3 GPa) and temperature (>2400 K), which mimic those generated by the infrared laser induction, it is possible to form crystallized layered graphene clusters from PI without the assistance of metal catalysts; this result is consistent with previous experimental observations; on the other hand, recent work show that if UV laser, instead of infrared laser, is used in the conversion process, only very poor quality graphene can be produced, due possibly to the poor absorption of UV light by the carbon source or unoptimized processing conditions.…”
Section: Introductionsupporting
confidence: 69%
“…[26] However, the underlying conversion mechanism for this method is still unclear, and the key parameters to ensure high-quality graphene are yet to be identified. A molecular dynamics (MD) simulation study by Dong et al suggests that under extreme conditions of high pressure (≈3 GPa) and temperature (>2400 K), which mimic those generated by the infrared laser induction, it is possible to form crystallized layered graphene clusters from PI without the assistance of metal catalysts; this result is consistent with previous experimental observations; [39] on the other hand, recent work [40,41] show that if UV laser, instead of infrared laser, is used in the conversion process, only very poor quality graphene can be produced, due possibly to the poor absorption of UV light by the carbon source or unoptimized processing conditions.In this study, we investigated in-depth the light-material interaction by developing a reactive MD model to disclose the transient process that leads to LIG formation and identified the critical parameters that govern this process. Following the theoretical prediction, we have experimentally demonstrated that picosecond UV laser processing can also be used to prepare high-quality LIG from PI at ambient conditions.…”
supporting
confidence: 74%
“…Such ISEs have therefore been implemented in a wide variety of applications including in situ water quality analysis, [ 3 ] electrolyte sensing in sweat, [ 4 ] and fertilizer monitoring in soils. [ 5 ] However, solid‐state ISEs are often prone to large signal drift, which may be caused by the formation of an aqueous layer between the ion‐selective membrane and the electrode. These sensors often require expensive materials such as noble metals or metallic nanoparticles to provide sufficient electrode conductivity and surface area for sensitive ion sensing.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene‐based electrodes hold tremendous promise for electrochemical biosensing including ion selective sensing [ 4c,5,6 ] due to their exceptional material properties, such as high electrical conductivity, strength, and ability to be functionalized with chemical moieties that are suitable for binding with a wide variety of biorecognition agents. [ 7 ] A variety of carbon‐based nanomaterials (i.e., fullerenes, carbon‐nanotubes, and graphene) have all been incorporated into solid‐state ISEs to increase electroactive surface of the electrode; ion‐selective membrane to electrode adhesion; and consequently, to improve signal sensitivity and stability while minimizing drift.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of the tested electrode is its very simple construction without an additional intermediate layer. [36] graphite powder Ppy(NO 3 À ) 5.4 × 10 À 5 1.5 × 10 À 4 -1.0 × 10 À 1 À 57.1 4.3-7.4 ClO 4 À , SCN À , Br À , I À , CN À [40] graphite TDMAN 3.0 × 10 À 5 5.0 × 10 À 5 -1.0 × 10 À 1 À 57.9 nr Cl À (ClO 4 À , SCN À Br À -nr) [37] MWCNTs TDMAN 2.5 × 10 À 6 3.2 × 10 À 6 -1.0 × 10 À 1 À 57.7 ClO 4 À , SCN À , NO 2 À , Cl À [39] TTFÀ TCNQ Nitrate ionophoreV 3.2 × 10 À 6 1.0 × 10 À 5 -1.0 × 10 À 1 À 58.5 nr NO 2 À (ClO 4 À , SCN À Br À -nr) [41] Laser induced graphene TDMAN 2.1 × 10 À 5 5.0 × 10 À 5 -1.0 × 10 À 1 À 54.8 nr nr [42] POTÀ MoS 2 nanocomposite TDMAN 9.2 × 10 À 5 7.1 × 10 À 4 -1.0 × 10 À 1 À 64.0 nr nr [35,43] DX262 NO 3 -ISE 3.0 × 10 À 5 3.0 × 10 À 5 -1.0 À 57.0 2-12 ClO 4 À , SCN À , Br À , I À , CN À , BF 4 À , salicylate this work Ag/AgCl/Cl À Co(Bphen) 2 (NO 3 ) 2 3.98 × 10 À 6 1.0 × 10 À 5 -1.0 × 10 À 1 À 56.3 5.4-10.6 ClO 4 À , SCN À , Br À TTFÀ TCNQ -tetrathiafulvaleneÀ tetracyanoquinodimethane; MWCNTs -miltiwalled carbon nanotubes; Ppy(NO 3 À ) -polypyrolle doped with nitrate; TDMAN -tridodecylmethylaminium nitrate; DX262 NO 3 -ISE -conventionalnitrate ISE offered by METTLER TOLEDO nr -not reported.…”
Section: Resultsunclassified